Pengelolaan Risiko Keuangan di Era Cryptocurrency: Pendekatan Komparatif terhadap Volatilitas Aset Digital dan Implikasinya bagi Portofolio Investasi Institusional - Abdul Rosid (Journal of Economics, Management, and Accounting, 2025)
The development of cryptocurrency as a highly volatile digital asset has changed the landscape of institutional investment risk management and created a need for a more adaptive risk management approach. This study aims to analyze the volatility, correlation, and downside risk of cryptocurrency compared to traditional assets, as well as evaluate the effectiveness of hedging strategies in institutional portfolios. Using a quantitative-comparative research method with historical data analysis for the 2020–2024 period, this study measures volatility, Value at Risk, Conditional Value at Risk, cross-asset correlations, and assesses the impact of cryptocurrency allocation on portfolio efficiency. The results show that cryptocurrencies have much higher volatility and tail risk than stocks, bonds, or gold, so the optimal allocation is a small portion, namely 3–5 percent. Hedging strategies such as futures, options, and dynamic hedging have been proven to reduce risk, but their effectiveness is greatly influenced by market conditions and liquidity. This study concludes that the integration of cryptocurrency into institutional portfolios is only feasible if supported by a strong risk management framework, real-time monitoring, and hedging strategies that are responsive to changes in volatility.